Perancangan Aplikasi Belajar Membaca Sebagai Media Pembelajaran Siswa TK Berbasis Android - Ari Irawan; Sutrisno Sutrisno; Agus Darmawan (Universitas Indraprasta PGRI Jakarta, 2022)
The need for a concept with an information technology (IT)-based learning mechanism has the impact of very rapid progress on the world of education. The concept which was later known as e-learning had the effect of transforming conventional education into digital form, both in terms of content and system. This study aims to develop a product in the form of Android-based mobile learning to support students' reading learning at the level of Kindergarten and equivalent education. The method used in this research is Research and Development (R&D) to develop products in the form of Android-based mobile learning. The results of this study are a prototype in the form of an Android-based Learning to Read Application as a learning media for students at Fatahilah Kindergarten Jakarta.